Trends in gastric cancer burden in the Western Pacific region from 1990 to 2021 and projections to 2040 - Zhang, Tao; Zhang, Yiqun; Leng, Xiaofei (Frontiers in Oncology, 2025)
BackgroundGastric cancer (GC) is a major public health concern, particularly in the Western Pacific, a high-incidence region that bears significant economic and social burdens.MethodsBased on data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2021, we conducted a comprehensive analysis of trends in the burden of GC in the Western Pacific from 1990 to 2021. We compared these trends with global and World Health Organization regional patterns, with a particular focus on geographic, gender, and age disparities. Health inequality was analyzed by comparing countries with different Socio-demographic Index (SDI) levels. Future trends in age-standardized rates were projected using the Bayesian Age-Period-Cohort (BAPC) model.ResultsThe GC burden of Western Pacific region remains above the global average, but improvements have outpaced global trends. China carries the highest burden, accounting for over half of regional cases, deaths, and disability-adjusted life years. While South Korea and Japan also experience high burdens, they have achieved notable reductions. Males consistently face higher burdens across age groups. Health inequality analysis shows narrowing gaps between high- and low-SDI countries, with the burden shifting toward less developed nations. BAPC model projections indicate a further decline in the GC burden by 2040.ConclusionDespite substantial progress in countries like Japan and South Korea, continued focus is needed on less developed regions to reduce the remaining GC burden in the future.